Archipelagic rhetoric: remapping the Marianas and challenging militarization from "A Stirring Place" - Na'puti, Tiara R. (Communication and critical/cultural studies, 2019)
Engaging critical rhetorical fieldwork in the Mariana Islands archipelago, this article destabilizes colonial naming projects and US federal control that dispossess island places from Indigenous peoples. On Euro-American and military maps, archipelagoes are depicted as distant, tiny, empty, or merely (is)lands for US geostrategic control. I argue for a remapping of the Marianas as expansive, oceanic sites of resistance to colonial cartographic violence and US militarization. Fieldwork in the Marianas demonstrates how Indigenous epistemologies function as archipelagic rhetoric enacted through a Chamoru sense of place. I examine these fluid relational connections to place and their implications for decolonization.